Ação do uso de fertilizantes de pronta e lenta disponibilidade na formação de mudas e crescimento inicial de Peltophorum dubium Spreng. Taub e Parapiptadenia rigida Vell. - Lang, Marcelo Junior (2007)
This study aimed to test the effects of fertilizing and containers in the production and initial growth of canafístula and angico seedlings. Seeds were sowed in September, 2005 in a protected area of Universidade Estadual do Oeste do Paraná, county of Marechal Cândido Rondon.The experimental design was a casualty blocks. Treatment were constituted of using a slow release fertilizer (Bascote 3m), a formulation used by ESALQ, and common substract (testimony) in containers of 120cm3 and 180cm3. The experiment was conductedin a nursery with five evaluations with intervals of20 days, and 4 field evaluations, three with 30 days intervals, and the fourth one year after planting.Measured variables in the nursery phase included: length, diameter, leaf area and dry mass , stem dry mass, root dry mass, above ground dry mass, root/shoot ratio, total dry mass and DICKSON s index. In the field, measured variables were: length, diameter and survival. In nursery, fertilizer and evaluation were the main causes of variations for angico seedlings. For canafístula seedlings fertilizier and container volume were causes of variation. Angico seedlings fertilized with Basacote resulted in 1.149 g, 0.806g with Esalq s formulation while the control seedlings weight increase was 0.657g of total dry mass; for canafistula seedlings the total dry mass increase were 1.155g with Basacote, 0.557 g with Esalq s formulation, and 0,492g for the control seedlings. It was observed that 80 days after emergence absolute growth index od seedlings decreased. Thirty days after planting,angico seedlings fertilized with Basacote presented length increase of 32.80 cm, with Esalq s formulation 23.04 cm, and the control seedlings 16.28cm. The increase of length expressed by canafístula seedlings was 28.05 cm with Basacote, 23.18cm with Esalq s formulation, and 17.16 cm with the contro seedlings.There are no effects from fertilizers in seedlings from small containers (i.e.120 cm3) 30 days after planting. Seedlings producedwith slow release fertilizer can be outplanted 20 days earlier than seedlings produced with other form of fertilization